Quantitative verification of the turbulence barrier effect during heavy haze pollution events. (1st April 2022) - Ren, Yan; Zhang, Hongsheng; Zhang, Xiaoye; Wu, Bingui; Cai, Xuhui; Song, Yu; Zhu, Tong
Abstract: Under calm and steady weather conditions with low wind speeds, turbulent intermittency frequently occurs in the atmospheric boundary layer (ABL), which can significantly weaken the turbulent diffusion of matter and energy between the surface and atmosphere. The turbulence barrier effect is defined as the phenomenon in which turbulence may disappear at certain heights, and during periods of heavy haze, creating what can seem like a barrier layer that hinders vertical transmissions. Although the turbulence barrier effect can explain the physical mechanisms behind the rapid accumulation of PM2.5 (fine particulate matter with diameters smaller than 2.5 μ m) and the influence of turbulent diffusion conditions on the vertical distribution of PM2.5, more direct perspectives such as turbulent flux is still required for quantitative verification. Due of challenges in the acquisition of PM2.5 turbulent flux, carbon dioxide (CO2 ), which has relatively mature flux acquisition technology, was used as a substitute means of verifying and quantifying this phenomenon. The turbulence data collected during heavy haze events, at from five levels of a 255 m meteorological tower located in Tianjin, were analyzed and used to quantitatively verify the influence of the turbulent barrier effect on PM2.5 . The results also revealed that the vertical changes in the turbulent barrier effect were consistent with those of the concentrations and flux of CO2 . This means that this knowledge about the turbulent barrier effect can be extended to other mass-transfer processes. The analysis also found that the proportion of counter-gradient transport increases when the occurrences of the turbulent barrier effect are frequent. This work validates the presence of the turbulent barrier effect and is an important foundation for its future parameterization, which will help to accurately identify the matter transport processes in the stable boundary layer and under extreme weather conditions, such as intense pollution events.